Oral‐bacterial‐induced arterial and venous thrombus in rats: Pathological and immunological studies - Takehisa Iwai; Yoshiki Matsui; Kaori Homma; Tamiko Takemura; Mutsunori Fujiwara; Norio Aoyama; Hiroki Sato; Yuichi Izumi (Wiley, 2019)
Abstract Objectives Our study investigated the pathological outcome of experimental thrombi that incorporate oral bacteria. Material and methods A small artery and vein in the rats' groins were injected with a solution containing periodontal bacteria Porphyromonas gingivalis and followed up for 28 days. In all, 18 limbs of nine male rats (500-650 g) were used for the arterial study, and eight limbs of four rats were used for the veins. Two densities of the bacterial solution and two arterial thicknesses sizes were used in the arterial study. Both proximal and distal arteries and veins were ligated loosely using a monofilament nylon suture before bacterial suspensions or control solutions were injected into the ligated vessels. Results After 7, 14-18, and 28 days, the rats were sacrificed. Pathology and immunohistochemistry were performed. All specimens exhibited thrombus formation and an acute inflammation reaction with granulocytes at 7 days and then settled down to chronic fibrous change with plasma cells or macrophages at 28 days in the arterial thrombus. CD3 (Pan T‐cells), CD79a (Pan B cells in the rats), and IgG were observed in the process of the healing of the arterial thrombus. Venous changes showed relatively clear recanalization that appeared at 7 days, which is slightly different from the artery. Granulocytes were present from 7 to 28 days. Conclusions Periodontal bacteria act as an inflammatory core in the vessels, but not as an infectious agent, in our experiments, because of their low ability to invade tissues.